Budidaya Hidroponik Posyandu Mawar Desa Palioi Kecamatan Kindang Kabupaten Bulukumba - Anita Anita (Jurnal Nasional Pengabdian Masyarakat, 2020)
Posyandu (Integrated Service Post) is a form of community self-help activity in the health sector whose existence is expected to bring promotive and preventive efforts closer to the community. Based on the output of the survey conducted at Posyandu Mawar, located in Palioi Village, Kindang District, Bulukumba Regency, it was found that there is still minimal use of posyandu land for vegetable cultivation. One method solution to solving the problem of Posyandu Mawar cadres is conducting hydroponic training. Hydroponics is the cultivation of planting using water without using soil but emphasizes more on meeting nutritional needs for plants. The method used uses interactive lecturing techniques using power point media. The materials provided are: (a) Definition of Hydroponics, (b) Excess Hydroponics, (c) Procurement of Hydroponic planting media, (d) Types of Hydroponic Plants, (e) Maintenance of Hydroponic Plants, (f) Hydroponic Harvesting. Training activities and practice of making hydroponics have been carried out with the output of this Community Partnership Program, namely Posyandu Mawar cadres who understand hydroponic vegetable cultivation and are able to practice it.